Developing Strategic Training Infrastructure to Support the Certification of Disease Intervention Professionals - Kathleen Pfohl; Leonardo Shanta Parker; Marlene Kincaid (Public Health Reports®, 2026)
Disease intervention professionals possess the critical skills and competencies necessary to prevent, manage, and control the spread of infectious diseases. However, until recently, no national credential existed to formally recognize their expertise. Through funding from the Centers for Disease Control and Prevention awarded to the Association of Schools and Programs of Public Health, the National Coalition of STD Directors was subawarded to support a national credentialing initiative designed to train and prepare disease intervention professionals for certification and recertification. The National Coalition of STD Directors advanced this initiative through the strategic development of a comprehensive, multimodal training pathway that aligns with the foundational elements of the Certified in Disease Intervention (CDI) program. This training pathway includes a 12-part eLearning module series, supplemental resources such as podcasts and micro-learning videos, a cobranded learning management system portal, and an interactive CDI educational summit. The strategic program plan developed under this initiative is guided by an evaluation framework to assess the reach, quality, and impact of the deliverables. Through the deployment of adult learning theories and insights from the public health field, this strategic training pathway provides disease intervention professionals with accessible, high-quality opportunities to strengthen their knowledge and skills as they prepare for certification and recertification under the CDI program.